Proper names with a sports origin in the urban space of Lodz - Grochala, Beata (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The article presents the names of Lodz streets with a sports origin and proper names of sports facilities. The material was excerpted from the Słownik nazewnictwa miejskiego Łodzi and from the website of the City of Łódź Office. The names were subjected to a semantic and structural analysis.